Hydrodynamic Red Blood Cells Deformation by Quantitative Phase Microscopy and Zernike Polynomials - Memmolo, Pasquale; Miccio, Lisa; Merola, Francesco; Mugnano, Martina; Ferraro, Pietro (Frontiers in Physics, 2019)
Red Blood Cells (RBCs) deformability is an important parameter for evaluating their health status. Its quantification is performed through the measurement of erythrocyte's shape stiffness when subjected to external stimuli. Here, we exploit the hydrodynamic deformation of RBCs in microfluidic channels to quantify the shape variations through quantitative phase imaging by digital holography. In particular, two main processing steps have been employed, i.e., the morphological analysis based on quantitative phase variations and a new way to monitor the entire cell's deformation, based on modeling RBCs as a micro-lenses array. In fact, taking advantage of the RBC lens behavior, it is possible to correlate optical aberrations generated by the mechanical stimulus to the entire membrane deformation itself, through a numerical analysis based on Zernike polynomials. We provide a proof of principle of how to use Zernike analysis for characterizing RBCs' deformability under hydrodynamic stress. We demonstrate that new optical parameters of RBCs can be measured and analyzed, thus opening the route to the exploitation of the bio-lens model as a biomechanical marker of RBCs.